Montaigne e a política - Conceição, Gilmar Henrique da (2010)
Commonly, human nature is considered unknown for Montaigne once we are all impregnated and bypassed customs, but poses different problems Montaigne inquiring about the possibility of political actions that enable a company to remain in balance and be improved, in spite of evil present in human nature perceived inconsistency of reason, and parties in conflict. Note that considers possible to improve the state of imperfection of man, but better does not mean eliminate the imperfection. Montaigne considers herself fully and visibly facing out, born to society and friendship (III, 3, p. 55) and broods primarily about state affairs and the world: "[...] haul me to the matters State and the universe best pleased when I'm alone "(III, 3, 56). He rejects the idealization of society, the best policy is one that exists. But, we highlight two jobs that makes the word politics: the first as "obligation to the public good", the second as "the practice of governments." Anyway, consider that living out of politics is to live outside of humanity and did not neglect public duties. Indeed, in Montaigne does not find the word with an unambiguous policy. In view of Montaigne is not possible absolute judgments in politics only because we share and we can not be located entirely outside of any particular perceptive condition to examine whether, on the one hand, the things themselves, and the other the way they present themselves in each one of those circumstances. The argument considers the act of "taking sides" involves, in itself, a presumption of knowledge, then he invites us to observe that this same assumption is present despite our view oscillates between the conflicting views that the ever, we hold as if they had, in general, a strength greater than they can reveal if considered over time. From this we can see that he discusses the political certainties given the insecure nature of the intellectual faculty, who frequently receives false things, hence the need for "moderation" and "dialogue" between the parties. So there is a questionable character in all parties. Unlike the certainty of "I just know that I know nothing" and "I think therefore I am ', Montaigne takes on the motto of Pyrrhus (" Que sais-je? ") which expresses most clearly mark the position of our author.